2023
DOI: 10.3389/fpsyt.2023.1206805
|View full text |Cite
|
Sign up to set email alerts
|

Home-administered transcranial direct current stimulation with asynchronous remote supervision in the treatment of depression: feasibility, tolerability, and clinical effectiveness

Theodoros Koutsomitros,
Sandra A. Schwarz,
Kenneth T. van der Zee
et al.

Abstract: Introduction (Background)Depression is an often chronic condition, characterized by wide-ranging physical, cognitive and psychosocial symptoms that can lead to disability, premature mortality or suicide. It affects 350 million people globally, yet up to 30% do not respond to traditional treatment, creating an urgent need for novel non-pharmacological treatments. This open-label naturalistic study assesses the practical feasibility, tolerability, and clinical effectiveness of home-administered transcranial dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Capacity for remote use invites a broader and more accessible intervention, but it also risks inconsistencies in use when it is self-administered by the participant rather than the research staff. These challenges may be mitigated by requiring hands-on pre-intervention training for research participants to learn and practice with the technology and real-time monitoring of treatment fidelity through videoconferencing [ 72 , 73 , 74 , 75 , 76 ]. A single center reported findings from its studies involving 6779 participants who underwent remotely supervised tDCS and found no serious adverse events, few study discontinuations due to tolerability (0.04%), and there was high treatment fidelity (92–98%) [ 75 ].…”
Section: Tdcs Mechanism Considerations and Other Usesmentioning
confidence: 99%
See 1 more Smart Citation
“…Capacity for remote use invites a broader and more accessible intervention, but it also risks inconsistencies in use when it is self-administered by the participant rather than the research staff. These challenges may be mitigated by requiring hands-on pre-intervention training for research participants to learn and practice with the technology and real-time monitoring of treatment fidelity through videoconferencing [ 72 , 73 , 74 , 75 , 76 ]. A single center reported findings from its studies involving 6779 participants who underwent remotely supervised tDCS and found no serious adverse events, few study discontinuations due to tolerability (0.04%), and there was high treatment fidelity (92–98%) [ 75 ].…”
Section: Tdcs Mechanism Considerations and Other Usesmentioning
confidence: 99%
“…A single center reported findings from its studies involving 6779 participants who underwent remotely supervised tDCS and found no serious adverse events, few study discontinuations due to tolerability (0.04%), and there was high treatment fidelity (92–98%) [ 75 ]. Remote tDCS has been used in studies of a wide variety of neuropsychiatric conditions including multiple sclerosis [ 72 ], Parkinson’s disease [ 74 ], major depressive disorder [ 76 ], depression, [ 77 ], and stroke [ 78 ], to name a few.…”
Section: Tdcs Mechanism Considerations and Other Usesmentioning
confidence: 99%